Taylor Rules and Macroeconomic Instability or How the Central Bank Can Pre-empt Sunspot Expectations - Mark Weder (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2003)
This paper derives new results on the effects of employing Taylor rules in economies that are subject to real market imperfections such as production externalities. Taylor rules that aggressively respond to output can eliminate sunspot equilibria that arise from the increasing returns. The paper also finds that rules which should be chosen (avoided) in perfect market environments often yield (ensure) multiple (unique) rational expectations solutions in alternative settings. Therefore, exact knowledge on the degree of market imperfection may be pivotal for robust policy advice.
urn:nbn:de:kobv:11-10050847
Keywords: 330; Geldpolitik; Taylor-Regel; Sunspot; Konjunktur; Theorie